Springback Analysis For Land Width Optimization In Cold Drawing Process Of Square Sectional Seamless Tubes - Dr. D.B. Karanjule, Dr. S. S. Bhamare (International Journal of Advanced Science and Technology, 2020)
Seamless tubes manufacturing process by cold drawing process achieves outer diameter, inner diameterand thickness of the tubes as per requirement. This paper emphasizes on the problem of springback effecton square cross sectional seamless steel tubes faced in the production with different land widths. Theexperimental study is carried for the analysis and modification on land width or bearing length of the diein controlling the springback of square sectional seamless steel tubes. This study deals with the effect ofland widths of 5, 10, 15 and 20 mm on springback by conducting experimentation and finite elementanalysis using ANSYS. The results of this study reveals that 10 mm is optimum land width to minimizespringback in square sectional tubes. This research improved springback results with the aid of series ofexperimentation. The results of this study reduced the rejection of precision tubes by 3 % saving substantialand considerable amount of the cold drawing manufacturing industry.